Streamlining the environmental impact assessment process of underwater noise from petroleum exploration and production operations - Erbe, Christine (Society of Petroleum Engineers, Inc., 2012)
Underwater noise is increasingly being considered a water quality indicator by governments around the world and plays an increasing role in environmental impact assessments of marine industrial developments. To-date, however, there are no standards for the measurement of underwater noise from petroleum operations, nor for data analysis, nor for reporting. As a result, the quality of many environmental impact assessments is poor, the results are not reliable, data are not comparable, errors (which are hardly ever assessed or reported) are huge, outcomes (e.g. impact zones, imposed mitigation requirements) are arbitrary and costs are as unpredictable as the lottery. The Centre for Marine Science & Technology at Curtin University is currently developing guidelines for underwater noise assessments with support from Chevron Australia. As a first step, we have reviewed international regulation of underwater noise from petroleum operations finding large disagreement in methodology and approaches, criteria and threshold levels, acoustic quantities assessed, and imposed mitigation paradigms. Commonalities include requirements for baseline sound measurements, anthropogenic noise source characterization and monitoring of marine life.